Spatial distribution and interannual variability of coastal fog and low clouds cover in the hyperarid Atacama Desert and implications for past and present Tillandsia landbeckii ecosystems - Del Río, Camilo; Lobos-Roco, Felipe; Latorre, Claudio; Koch, Marcus; García, Juan-Luis; Osses, Pablo; Lambert, Fabrice; Alfaro, Fernando D.; Siegmund, Alexander (Plant systematics and evolution, 2021)
The hyperarid Atacama Desert coast receives scarce moisture inputs mainly from the Pacific Ocean in the form of marine advective fog. The collected moisture supports highly specialized ecosystems, where the bromeliad Tillandsia landbeckii is the dominant species. The fog and low clouds (FLCs) on which these ecosystems depend are affected in their interannual variability and spatial distribution by global phenomena, such as ENSO. Yet, there is a lack of understanding of how ENSO influences recent FLCs spatial changes and their interconnections and how these variations can affect existing Tillandsia stands. In this study, we analyze FLCs occurrence, its trends and the influence of ENSO on the interannual variations of FLCs presence by processing GOES satellite images (1995-2017). Our results show that ENSO exerts a significant influence over FLCs interannual variability in the Atacama at ~ 20°S. Linear regression analyses reveal a relation between ENSO3.4 anomalies and FLCs with opposite seasonal effects depending on the ENSO phase. During summer (winter), the ENSO warm phase is associated with an increase (decrease) of the FLCs occurrence, whereas the opposite occurs during ENSO cool phases. In addition, the ONI Index explains up to ~ 50 and ~ 60% variance of the interannual FLCs presence in the T. landbeckii site during summer and winter, respectively. Finally, weak negative (positive) trends of FLCs presence are observed above (below) 1000 m a. s. l. These results have direct implications for understanding the present and past distribution of Tillandsia ecosystems under the extreme conditions characterizing our study area.
Gesehen am 11.11.2021